Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism